Über die Wassermassentransformation im Europäischen Nordmeer: Prozess-Studien und Budgets - Latarius, Katrin (2013)
Within the Arctic Mediterranean the inflowing warm and saline Atlantic Waters are transformed into cold and relatively fresh, dense overflow waters, which flow back into the North Atlantic at depth. The major part of the transformation takes place in the ice-free areas of the Nordic Seas. This investigation examines the contribution of the deep basins in the Nordic Seas to the overall transformation. Since 2001 hydrographic measurements with profiling floats were conducted in the Nordic Seas. This data set provides insight into the temporal development of the hydrography in the four deep basins (Norwegian Basin, Lofoten Basin, Greenland Sea and Icelandic Plateau). In the study on hand the data are used to describe the variability of the hydrography on seasonal and inter-annual to decadal time scales. In combination with sea surface flux data heat and freshwater budgets for the basins are established. Based on the budgets the relative importance of the deep basins for the water mass transformation is estimated. Time series of temperature and salinity for the basins are dominated by the seasonal signal in the upper 500 to 750 m. Amplitudes are up to 2.5°C. A harmonic analysis is used to separate it from the signals on longer time scales. The detailed knowledge of the seasonal signal can be used for the analysis of longer-term variability on the basis of historical data. Without a seasonal correction there is a risk of misinterpretation due to aliasing, because data were mainly taken in the summer month. With a maximum total length of the time series of 11 years the separation of inter-annual and decadal variability is mathematically not possible. However the temperature and salinity development in the Greenland Sea and the Norwegian Basin is interpreted in relation to the propagation of decadal to multi-decadal anomalies in the properties of the inflowing Atlantic water around the Nordic Seas, which was analyzed in other studies. Furthermore the time series from the Greenland Sea demonstrate the decay of the ...